Titanium-dioxide nanostructures grown by dual DC/HiPIMS for dye-sensitized solar cell applications - Grigorov,K. (2020)
Abstract This work reports how the solar conversion efficiency of dye-sensitized solar cells (DSSCs) depends on the crystalline structure of both the compact TiO2 blocking layer (BL) and homoepitaxially grown porous TiO2 mesoporous structure. The films were grown by simultaneous sputtering of titanium targets by DC magnetron and by high-power impulse magnetron systems (HiPIMS). The deposition conditions were managed to produce in situ dense BLs and porous TiO2 films. The only variable was the polarization of the BLs (0 to -200V). The polarization caused phase transformations from pure anatase phase through rutile-anatase mixed phases to rutile phase. The polarization results in decreasing intensity of the anatase (101) peak of the porous layers. The latter promptly decreased linearly the value of the short-current Isc and exponentially the open-circuit voltage Voc of the cells. Another inference is the surface energy of the BLs, which follows an exponential decay as a function of the film polarization. XPS study of the Ti 2p3/2 – Ti 2p1/2 doublet reveals an appearance of a shake-up satellite, whose area exponentially decreases as the polarization potential rises. This phenomenon is discussed and related with other physical aspects of the homo-epitaxially grown films with different texture. The anatase phase content and its purity predefined by the experimental conditions determine the quality of the DSSC, as well as other components such as the dye type, the electrolyte, and the electrode materials.